Enumeration of rooted biloopless planar maps - Long, Shude; Cai, Junliang (Utilitas Mathematica, 2020)
In this paper we investigate the number of rooted biloopless planar maps and present three formulae for such maps with some or all of the following parameters: the number of edges and the valency of the root-face (root-vertex). © 2020 Utilitas Mathematica Publishing Inc.. All rights reserved.